Dominant ACO2 mutations are a frequent cause of isolated optic atrophy. Issue 2 (7th April 2021) - Charif, Majida; Gueguen, Naïg; Ferré, Marc; Elkarhat, Zouhair; Khiati, Salim; LeMao, Morgane; Chevrollier, Arnaud; Desquiret-Dumas, Valerie; Goudenège, David; Bris, Céline; Kane, Selma; Alban, Jennifer; et al.
Abstract: Biallelic mutations in ACO2, encoding the mitochondrial aconitase 2, have been identified in individuals with neurodegenerative syndromes, including infantile cerebellar retinal degeneration and recessive optic neuropathies (locus OPA9). By screening European cohorts of individuals with genetically unsolved inherited optic neuropathies, we identified 61 cases harbouring variants in ACO2, among whom 50 carried dominant mutations, emphasizing for the first time the important contribution of ACO2 monoallelic pathogenic variants to dominant optic atrophy. Analysis of the ophthalmological and clinical data revealed that recessive cases are affected more severely than dominant cases, while not significantly earlier. In addition, 27% of the recessive cases and 11% of the dominant cases manifested with extraocular features in addition to optic atrophy. In silico analyses of ACO2 variants predicted their deleterious impacts on ACO2 biophysical properties. Skin derived fibroblasts from patients harbouring dominant and recessive ACO2 mutations revealed a reduction of ACO2 abundance and enzymatic activity, and the impairment of the mitochondrial respiration using citrate and pyruvate as substrates, while the addition of other Krebs cycle intermediates restored a normal respiration, suggesting a possible short-cut adaptation of the tricarboxylic citric acid cycle. Analysis of the mitochondrial genome abundance disclosed a significant reduction of the mitochondrial DNA amount in all ACO2 fibroblasts. Overall, our data position ACO2 as the third most frequently mutated gene in autosomal inherited optic neuropathies, after OPA1 and WFS1, and emphasize the crucial involvement of the first steps of the Krebs cycle in the maintenance and survival of retinal ganglion cells. Abstract : By screening European cohorts of individuals with genetically unsolved inherited optic neuropathies, Charif et al. report 61 new cases harbouring variants in ACO2, among whom 50 with dominant mutations, emphasizing for the first time the important contribution of ACO2 monoallelic pathogenic variants to dominant optic atrophy. Graphical Abstract: